Designing our way to a better world - Fisher, Thomas (University of Minnesota Press, 2017)
'Designing Our Way to a Better World' challenges the assumptions that have led to so much poor performance in the public and private realms: that our schools cannot teach creativity, that our governments cannot predict the disasters that befall us, that our health system will protect us from pandemics. Targeting these assumptions, Thomas Fisher's approach reveals the power of design to synthesize our knowledge about the world into greater wholes.